The Role of Cognitive Emotion Regulation Strategies in Problem Gaming Among Adolescents: A Nationally Representative Survey Study - Kökönyei, Gyöngyi; Kocsel, Natália; Király, Orsolya; Griffiths, Mark D.; Galambos, Attila; Magi, Anna; Paksi, Borbála; Demetrovics, Zsolt (Frontiers in Psychiatry, 2019)
Explanatory theoretical models have proposed an association between problematic online gaming and abilities or strategies in alleviating distress or negative emotions in times of stress as proximal non-gaming related personality factors. However, there is a little research which has targeted how emotion regulation relates to problematic online gaming – especially during adolescence when gaming behavior is most prevalent. In emotion regulation research, there has been a particular emphasis on rumination because it is strongly associated with overall psychopathology. However, it is unknown whether this putatively maladaptive strategy relates to problematic online gaming and whether it is a gender-dependent association. Consequently, the present study examined how emotion regulation strategies, and particularly rumination, related to problem gaming and to test whether gender moderated this relationship in adolescents. In a national representative adolescent sample, 46.9% of the participants (N=1646) reported online gaming in the past 12 months and provided information on problematic gaming and it was these data that were used for further analysis. Their data concerning problematic online gaming and emotion regulation strategies were analyzed, including rumination along with other putatively maladaptive (e.g., catastrophizing) and adaptive (e.g., positive reappraisal) strategies, while controlling for age, gender, and game genre preference. Results of linear regression analyses showed that all the putatively maladaptive emotion regulation strategies (including self-blame, other blame, catastrophizing and rumination) were positively related to problematic online gaming. Positive reappraisal proved to be a protective factor, it was inversely related to problematic online gaming. In addition, the relationship between rumination and online gaming was moderated by gender (i.e., the relationship was stronger among boys). Based on the results, it is argued that emotion regulation is a useful framework to study problematic online gaming. The present study highlighted the relative predictive value of rumination for problematic online gaming varied for boys and girls, suggesting that trait rumination might be a gender-specific vulnerability factor for problematic online gaming, but this requires further investigation and replication.